The flare of care for rare: per aspera ad astra for rare lung diseases! - Wijsenbeek-Lourens, Marlies; Humbert, Marc; Wagner, Thomas; Kreuter, Michael (European respiratory review, 2023)
For rare lung diseases cross border collaborations and joining forces, such as between ERN-LUNG and ERS as well as patient organisations, are crucial to improve diagnosis and management of these diseases.
Gesehen am 07.12.2023